Intelligent pervasive computing systems for smarter healthcare - Sangaiah, Arun Kumar 1981-; Shantharajah, S. P.; Theagarajan, Padma (Wiley, 2019)
"This book describes the innovations in healthcare made possible by computing through bio-sensors. The reader learns how that goal is being pursued by the editors' examination of topics such as the design and development of pervasive healthcare technologies, data modeling and information management, wearable biosensors and their systems, and more. The pervasive computing paradigm offers tremendous advantages in diversified areas of healthcare research and technology. Pervasive computational support enables the optimization of medical assessment for a healthier, safer, and more productive society"--
Keywords: Medical care / Data processing; Ubiquitous computing; Medical electronics